Growth Performance and Histological Changes in Ileum and Immune Related Organs of Broilers Fed Organic Acids or Antibiotic Growth Promoter - Mohamed, M.A.; El-Daly, Eman F.; El-Azeem, Nafisa A. Abd; Youssef, Amani W.; Hassan, H.M.A. (International Journal of Poultry Science, 2014)
An experiment was designed to evaluate the effects of using organic acids as an alternative to antibiotic growth promoter on performance of broiler chicks. Carcass characteristics, histological changes of ileum and immune related organs (bursa, thymus and spleen) along with intestinal bacteria count were also studied. A number of 150 Cobb broiler chicks were fed on three dietary treatments: a basal corn-soybean meal diet served as a control treatment with no supplements or supplemented with either 0.025% Bacitracin Methylene Disalicylat (BMD, antibiotic) or 0.06% Galliacid® (organic acids) from 10 to 36 days of age. The results showed that birds fed antibiotic or organic acids gained significant (p<0.05) more body weight than those fed the control diet. No significant differences were detected among treatments on feed intake while feed conversion ratio (FCR) values were significantly (p<0.001) differ. Addition of organic acids or antibiotic did improve FCR by about 9 and 4%, respectively. These results indicated that birds fed either organic acids or antibiotic supplemented diets utilized feed more efficiently than those fed the control diet. Carcass characteristics were not affected by dietary treatments, while the addition of antibiotic or organic acids significantly (p<0.01) increased spleen and bursa weight (% live body weight). Addition of organic acids was more effective than antibiotic on decreasing intestinal count of Escherichia coli and appearance of Colostridium perfringers. Organic acids as alternative to the antibiotic growth promoter have stimulated some histological change in histology of the villi and the immune related organs. Performance and feed efficiency are closely interrelated with the quantitative microbial load of the gut, the morphological structure of the intestinal wall and the activity of the immune system. In conclusion, dietary inclusion of organic acids increased growth performance and improved intestinal health and morphology of broiler chicks. It could be successfully used as alternative to antibiotic growth promoters in broiler diets or as a tool of controlling intestinal pathogenic bacteria.